2019
DOI: 10.1261/rna.070433.119
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of ribonuclease 1 deficiency in mice

Abstract: Biological roles for extracellular RNA (eRNA) have become apparent. For example, eRNA can induce contact activation in blood via activation of the plasma proteases factor XII (FXII) and factor XI (FXI). We sought to reveal the biological role of the secretory enzyme ribonuclease 1 (RNase 1) in an organismal context by generating and analyzing RNase 1 knockout (Rnase1-/-) mice. We found that these mice are viable, healthy, and fertile, though larger than Rnase1 +/+ mice. Rnase1-/plasma contains more RNA than do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…Additionally, prothrombotic eRNA was also associated to fibrin-rich thrombi in an arterial thrombosis mouse model and pretreatment of mice with RNase1 considerably reduced eRNA containing thrombi and delayed vessel occlusion (Kannemeier et al, 2007). These findings are in line with the phenotype of recently described RNase1 deficient mice that showed increased eRNA plasma levels and more rapid blood clotting, indicating a crucial role for RNase1 in regulation of blood coagulation (Garnett et al, 2019).…”
Section: Atherosclerosis and Thrombosissupporting
confidence: 78%
“…Additionally, prothrombotic eRNA was also associated to fibrin-rich thrombi in an arterial thrombosis mouse model and pretreatment of mice with RNase1 considerably reduced eRNA containing thrombi and delayed vessel occlusion (Kannemeier et al, 2007). These findings are in line with the phenotype of recently described RNase1 deficient mice that showed increased eRNA plasma levels and more rapid blood clotting, indicating a crucial role for RNase1 in regulation of blood coagulation (Garnett et al, 2019).…”
Section: Atherosclerosis and Thrombosissupporting
confidence: 78%
“…Clearly, biofluids are a much more complex environment than conditioned medium from cultured cells. However, considering that at least in plasma, RNase 1 constitutes the majority of ribonucleolytic activity ( 82 ), our results position RNase 1 as a likely candidate for producing extracellular tRNA halves and Y RNA fragments in vivo . Future studies will have to validate this, as well as address the functional and diagnostic relevance of these extracellular fragments.…”
Section: Discussionmentioning
confidence: 74%
“…While the catalytic mechanism of RNase 1 has been studied in detail, the role of this enzyme remains less well defined. Several studies have suggested RNase 1 as a scavenger of extracellular RNA, involved in immunomodulation and modulation of coagulation ( 82–84 ). The results of our study suggest a novel role for RNase 1 as a factor involved in production of abundant extracellular tRNA halves and distinct Y RNA fragments.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is good evidence that cell-free DNA plays a crucial role in the crosstalk between tissue injury, inflammation, and coagulation, very little is known about the physiological and pathophysiological roles of eRNA in sepsis (27). It has been suggested that the negative charge of eRNA builds the structural feature rendering eRNA capable of activating factor XII and, hence, coagulation (28,29). Moreover, Chen and colleagues report that eRNA contributes to myocardial inflammation via TLR-3-Trif signaling (23).…”
Section: Discussionmentioning
confidence: 99%